Gabapentin for the Treatment of Vulvodynia: A Randomized Controlled Trial. Issue 6 (June 2018) - Brown, Candace S.; Bachmann, Gloria A.; Wan, Jim; Foster, David C.
Abstract : OBJECTIVE: To evaluate whether extended-release gabapentin is more effective than placebo among women with vulvodynia. METHODS: In a multicenter double-blind, placebo-controlled randomized crossover trial, gabapentin (1, 200–3, 000 mg/d) was compared with a placebo. The primary outcome was mean pain intensity (0, no pain at all to 10, worst pain ever) on the tampon test (a standardized tampon insertion and removal test used as a surrogate marker for dyspareunia) during the last 7 days of the maintenance phase. Secondary outcomes included sexual intercourse pain and daily pain. A sample size of 53 provided 90% power to detect a 1-point reduction on the tampon test (.05 level, two-sided) between the two treatment phases. RESULTS: From August 2012 to January 2016, 230 women were screened at three academic institutions and 89 (mean age 37 years; 65% black) were randomized: 45 to gabapentin first and then placebo and 44 to placebo first and then gabapentin. Tampon test pain with gabapentin was not different compared with the placebo (adjusted mean 4.0, 95% CI 3.0–4.9 vs 4.3, 95% CI 3.4–5.2, difference −0.3, 95% CI −0.7 to 0.0; P =.07). Gabapentin also did not improve pain over placebo for sexual intercourse pain (adjusted mean 3.9, 95% CI 2.4–5.3 vs 4.0, 95% CI 2.5–5.4, difference −0.1, 95% CI −0.9 to 0.6; P =.76) and daily pain (adjusted mean 2.7, 95% CI 1.8–3.6 vs 2.9, 95% CI 2.0–3.8, difference −0.2, 95% CI −0.5 to −0.2; P =.36). Subset analyses found that longer pain duration and oral contraceptive nonuse were associated with minimal improvement in tampon test pain with gabapentin. CONCLUSION: In this cohort, extended-release gabapentin, as compared with a placebo, did not reduce tampon test pain. These data do not support the recommendation of gabapentin alone as treatment for vulvodynia. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01301001. Abstract : Women with vulvodynia do not report decreased vulvovaginal pain as measured by the tampon test after gabapentin intervention.